Coexistence of communication signals and target detection for RadComm systems - Ang, Wei Quan (Nanyang Technological University, 2024)
In the burgeoning aircraft industry, Air Traffic Control (ATC) relies on two primary systems for managing air traffic: radar systems for aircraft detection and communication systems for pilot interaction. This report delves into the coexistence of radar and communication systems. Specifically, the radar system utilizes Linear Frequency Modulation (LFM) signals for target detection, while the communication system employs Binary Phase Shift Keying (BPSK) technique. This analysis entails the use of MATLAB programming to simulate target detection and communication signal modulation, aiming to obtain test results and assess system performance. The communication system's objective is to evaluate the Bit Error Rate (BER) post-interference with radar LFM signals. Meanwhile, the target detection objective encompasses examining range-speed response patterns and assessing how communication signals affect radar performance.